2019
DOI: 10.2147/clep.s201983
|View full text |Cite
|
Sign up to set email alerts
|

<p>Statin use and high-dose statin use after ischemic stroke in the UK: a retrospective cohort study</p>

Abstract: Background: Trial evidence supports statin use after ischemic stroke and recent American, European and British guidelines recommend high-intensity statins for this indication. Limited data are available describing current statin use among these patients in unselected settings. We conducted a cohort study to examine secular trends and factors associated with statin use and dose following ischemic stroke. Methods: A retrospective cohort study of patients with first ischemic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
2
14
1
2
Order By: Relevance
“…In our study, however, we found that a minority of these patients actually received high-intensity statin treatment. Underuse of high-intensity statin treatment is common in general practice [16][17][18], and several reasons may explain this finding. Statin-related sideeffects led to the discontinuation of treatment in 10% of patients [19], and Deshpande et al observed poorer patient adherence to high-intensity statin regimens when compared to lower intensity regimens [20].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, however, we found that a minority of these patients actually received high-intensity statin treatment. Underuse of high-intensity statin treatment is common in general practice [16][17][18], and several reasons may explain this finding. Statin-related sideeffects led to the discontinuation of treatment in 10% of patients [19], and Deshpande et al observed poorer patient adherence to high-intensity statin regimens when compared to lower intensity regimens [20].…”
Section: Discussionmentioning
confidence: 99%
“…As a general precaution, diabetes patients with eCVD should be closely monitored for control of their metabolic parameters and risk factors. Contemporary evidence from CPRD suggests that only 75% of patients (with or without diabetes) receive lipid-lowering therapy after a stroke [16]. Diabetes has been associated with a slightly higher rate of statin utilization.…”
Section: Discussionmentioning
confidence: 99%
“…For both smoking and BMI variables, the most recent data before the index stroke were used. Stroke subtype was classified into ischemic and hemorrhagic stroke (specific codes relating to ischemic stroke or unspecified stroke codes were regarded as ischemic stroke, considering these patients shared similar characteristics [ 19 ] and 90% of stroke in the UK is ischemic stroke [ 20 ]). Prior comorbidity was defined as the presence of any relevant Read code or ICD-10 code before the index stroke.…”
Section: Methodsmentioning
confidence: 99%